A Re-interpretation of Matthew Arnold's Empedocles on Etna and a Critical Discussion of His 1853 Preface - Dietrich, Udo Manfred (My University, 1973)
Matthew Arnold's Empedocles on Etna is a profound poem which touches on the fundamental problems of human experience. This study attempts to re-interpret the particular solutions to these problems advanced in the poem. A consideration of other works of literature which explore the same questions of life and death suggests that the suicide of Arnold's Empedocles is not an act of despair but a symbolic ritual of purification. In this light, a new reading of the poem discovers much internal evidence to support this view of it as a celebration of visionary calm. Arnold himself, however, repudiated Empedocles in the Preface to his next volume of poems, and he did not reprint it until fifteen years later. This study attempts to prove that Arnold's repudiation 1vas not based on any intrinsic defects in Empedocles or on the objections and complaints made against the poem by critics and re-viewers, but that it was rather the result of his intensely personal and painfully ambiguous relationship to the poem.
Keywords: English Language and Literature; English Language and Literature